Effect of variable viscosity on MHD inclined arterial blood flow with chemical reaction - Tripathi, Bhavya; Sharma, Bhupendra Kumar (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we present the mathematical study of heat and mass transfer effects on an arterial blood flow under the influence of an applied magnetic field with chemical reaction. A case of mild stenosis is considered in a non-tapered artery which is inclined at an angle from the axis. The variable viscosity of the blood is considered varying with the hematocrit ratio.
Keywords: magnetohydrodynamical fluid (MHD); Homotopy Perturbation Method (HPM); variable viscosity; chemical reaction